On existence and concentration of solutions to a class of quasilinear problems involving the 1-Laplace operator - Alves, Claudianor O.; Pimenta, Marcos T. O. [UNESP] (Springer Nature, 2017)
In this work we use variational methods to prove results on existence and concentration of solutions to a problem in RN involving the 1-Laplacian operator. A thorough analysis on the energy functional defined in the space of functions of bounded variation BV(RN) is necessary, where the lack of compactness is overcome by using the Concentration of Compactness Principle due to Lions.
Keywords: 35J20; 35J62